Cases in Financial Engineering: Applied Studies of Financial Innovation. - Triantis, Alexander J.; Mason, Scott P.; Merton, Robert C.; Perold, Andre F.; Tufano, Peter (Journal of Finance, 1995)
1. Financial Innovation and The Financial System. 2. Securities Innovation: A Historical and Functional Approach. CASES. 1. Financial Engineering and Debt Securities. 1.1 Arbitrage Fundamentals. Cougars. RJRCHC 1991. Arb in Government Bonds. Coca Cola–Harmless Warrants.1.2 Taxes, Regulation and Accounting: Stimuli to Innovation. Citicorp 1985. Note: Eurodollar Bond. New England Property and Casualty. Schroeders Perpetual. Metromedia.1.3 Securitization. Travelers. Note: MBS. Amex TRS Case. Lehman Case.2. Financial Engineering and Equity Securities. 2.1 Addressing Information Asymmetries. Arley. Avon PERCs. GM PERCs. ALZA series (A-B1-B2-C). British Telecom. RJR 1990. Sally Jameson.2.2 Taxes, Regulation and Accounting: Stimuli to Innovation. ARPPS. MMP. Dart and Kraft. Waste Management.3. Managing Issuers' Exposures. 3.1 Managing Issuers' Exposures. B.F. Goodrich-Rabobank. GM–Liab Management. State of CT Muni Swap. Walt Disney. Gaz de France. American Barrick. Enron.3.2 Managing Investors' Exposures. SLH (A&B). Goldman Sachs Nikkel Put Warrants. Commodity Linked Debt. Note: Commodity Futures. Fidelity Case. Diamond Shamrock Natomas. BEA Associates. LOR: Portfolio Insurance. LOR: SuperTrust.FOUNDATION NOTES. Note: U.S. Government Debt Markets. Note: Foreign Exchange. Note: FX Swaps. Note: Introduction to Options. Note: Option Pricing. Note: Contingent Claims Analysis. Note: Financial Futures. Note: Interest Rate Derivatives.